Creating Inclusivity: Adaptive Fashion and the Potential of Artifcial Intelligence in Its Design - Kukiełko, Kalina (Inclusive Digital Technologies: Perspectives, Opportunities, and Limitations, 2025)
Te chapter introduces the concept of adaptive fashion, which is crucial in promoting inclusivityand integrating people with disabilities, enabling their fuller participation in social and professionallife. According to data from the World Health Organization (WHO), over one billion peopleworldwide live with various forms of disabilities. Despite this number, the traditional fashionmarket primarily focuses on the needs of individuals with standard body types, leading to themarginalization of those whose bodies deviate from mainstream norms. Te lack of appropriatelyadapted clothing limits their choices, resulting in a sense of exclusion and reduced self-esteem,while fashion should fulfll both practical and aesthetic functions. In this context, artifcial intelligence(AI) plays an increasingly important role by opening new possibilities in designing adaptiveclothing. Trough advanced algorithms, AI enables better tailoring of garments to diverse bodyshapes, the selection of suitable materials, and the testing of innovative functional solutions thatmeet individual users’ needs. Te use of modern technologies allows for the creation of clothingthat not only ensures comfort and functionality but also enables the expression of individual styleand personality. In this way, adaptive fashion, supported by AI, can signifcantly contribute tobuilding a more inclusive fashion market that meets the needs of all members of society.